Los mentefactos en el desarrollo del pensamiento conceptual de los niños-as de séptimo año de educación básica de la escuela Tomás Martínez de la Hcda la Clementina Parroquia la Unión Cantón Babahoyo durante el periodo lectivo 2009-2010 - López Muñoz, Rodolfo Ezequiel (2010)
The investigation (research) of The Mentefactos, in the development of the conceptual thought of the children - aces of the seventh year of basic Education of the school Tomás Martínez of the Estate Clementine of the parish Snail of the Canton Babahoyo, Province of The Rivers, and period 2009-2010. Before the need to arouse the teachers of this institution it (he, she) brings over of the methodology of mentefactos and the development of the thought we do not find experimental information that allow confirming the utilization of mentefactos as potential pray of development of the conceptual thought in the children - aces. Accepted these limitations, basic beginning (principles) is summarized on the methodology of mentefactos and development of the thought and some recent offers it (he, she) brings over of his (her, your) functionality in the development of the thought. When the validity analyzes of this interrelationship, it is possible to presume that the development of the thought of the children is influenced by the opportunities that one presents to enrich such a process and the mentefactos demand (sue) intellectual operations. The information that have been obtained on the conceptual thought and the mentefactos, he(she) lacks experimental sufficient information that allow to establish with certainty the interrelationship that exists between(among) mentefactos and development of the thought. 14 Almost all the studies of development of the thought realized emphasize the need to enrich cognitive structure by means of stimuli and cognitive dilemmas since only by means of the exercise (fiscal year) we can improve our mental skill and in this investigation (research) after applied the instruments we could observe with enough approximation the lack of learnings that should promote this skill. Regarding development of the thought and for being related to one of the parts more complex of the human being since(as, like) it it is the brain still(yet) big emptinesss of knowledge exist, owed probably to the same complexity of the awkward factors (genetic, air of the cerebral bark, multiple, environmental intelligences, educational and the opportune nutrition of the brain), that impede his (her, your) evaluation and interpretation and, therefore the design of relevant investigations(researches) of the topic. Recognized the limitations that still(yet) exist in the treatment on mentefactos and the development of the thought, the present work emphasizes basic beginning(principles) on the intellectual operations that the production(elaboration) of the foolish persons demands(sues) and therefore his (her, your) contribution to the development of the conceptual thought. Previous a documentary review on the factors that diminish the probabilities of developing the conceptual thought. It hopes that the effort that we have formed in this work is a wealth-producing contribution to the work of the teachers and to the educational community I object of our worry and it is the beginning of change of routine bosses. We have not wanted but to look for strategies that simplify the educational work and that there helps us to change the mental scheme of our students turning them into competent agents. The task is of all and we try to be also a reflection (reflex) of what we express